Strategi Pemasaran Syariah di Tengah Persaingan Pasar Modern pada UMKM Toko Ikhlas di Nagari Koto Baru, Kec. IV Nagari, Kab. Sijunjung - Rifa Suganda; Awaluddin Awaluddin (Lembaga Yasin AlSys, 2026)
Sharia marketing strategies in micro, small, and medium enterprises (MSMEs) have received attention in several studies, but research that specifically discusses the integration of the marketing mix (4P) with the functions of sharia business management (POAC) in facing modern market competition remains limited. This study aims to analyze the implementation of sharia marketing strategies and their management from the perspective of sharia business management at Toko Ikhlas MSME in Nagari Koto Baru, IV Nagari Subdistrict, Sijunjung Regency. This study employed a qualitative approach with a case study design, involving the main informants, namely the business owner, employees, and customers selected through purposive sampling. Data were collected through in-depth interviews, direct observation, and documentation, and were then analyzed using interactive analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results showed that Toko Ikhlas had implemented sharia marketing strategies through the marketing mix, which includes product, price, place, and promotion, adjusted to community needs and sharia values such as honesty and justice. In addition, the functions of sharia business management, which include planning, organizing, actuating, and controlling, had been implemented, although they were still simple and had not yet been formally documented. These findings contribute to the development of sharia business management theory and broaden understanding of sharia marketing practices at the MSME level. The conclusion of this study affirms the importance of integrating sharia marketing strategies with systematic business management in facing modern market competition, while also indicating the need to enhance the use of digital technology and business planning among MSME actors.